2010
DOI: 10.1089/neu.2010.1456
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Motor Cortex after Controlled Cortical Impact in Rats and Implications for Functional Recovery

Abstract: We report the results of controlled cortical impact (CCI) centered on the caudal forelimb area (CFA) of rat motor cortex to determine the feasibility of examining cortical plasticity in a spared cortical motor area (rostral forelimb area, RFA). We compared the effects of three CCI parameter sets (groups CCI-1, CCI-2, and CCI-3) that differed in impactor surface shape, size, and location, on behavioral recovery and RFA structural and functional integrity. Forelimb deficits in the limb contralateral to the injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 68 publications
7
92
1
2
Order By: Relevance
“…Rats in all three groups received a CCI injury over the M1 forelimb area (5). Postmortem histological analysis confirmed that lesion size was comparable across groups (SI Results).…”
Section: Methodsmentioning
confidence: 76%
See 3 more Smart Citations
“…Rats in all three groups received a CCI injury over the M1 forelimb area (5). Postmortem histological analysis confirmed that lesion size was comparable across groups (SI Results).…”
Section: Methodsmentioning
confidence: 76%
“…2A). After forelimb preference was determined, a removable Plexiglas wall was used to force the animal to use only the preferred forelimb (5). Trials were recorded with a digital camcorder for playback and analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of TBI are by nature heterogeneous, but moderate-to-severe TBIs can result in chronic deficits in motor function [77,78]. Recovery of motor function is associated with plasticity in spared motor circuits [79][80][81], and VNS paired with rehabilitation may enhance this plasticity to support recovery. Pruitt et al [82] evaluated whether VNS therapy could improve recovery of motor function in a controlled cortical impact model of severe TBI.…”
Section: Preclinical Studies For Traumatic Brain Injurymentioning
confidence: 99%